Analyzing curriculum materials from a gender perspective: Grade eight English textbook of Ethiopia in focus - Mulugeta Yayeh Worku (College of education, Bahir Dar University, 2023)
The purpose of this study was to examine the place of some gender issues in curriculum materials of Ethiopia. To achieve this purpose, a qualitative content analysis was made on the country's Grade Eight English textbook. The analysis was conducted on two interrelated categories: nature of narrations and sensitivity of illustrations. In doing so, a nine-stage content analysis model, developed by Frankel and Wallen (2006), was employed. The analysis revealed that in all of the evaluation criteria, the textbook was gender-biased favoring the male gender. For instance, most of the passages and stories presented in the textbook were narrating the fame, contributions, and achievements of the masculine gender. The study also revealed that the great majority of the role models in the textbook under consideration were representing the male gender. Besides, most of the illustrations presented in the textbook were male-dominated that convey unequal power relationships between the two genders. Overall, from the findings of the present analysis, it was understood that some gender issues that need to be considered while writing a language textbook were not adequately addressed. Finally, the implications of these findings for future research and policy initiatives are briefly indicated.